Perbandingan Pendapatan Usahatani Padi Organik dan Padi Anorganik di Desa Watukebo, Kecamatan Blimbingsari Kabupaten Banyuwangi - Dhimas Rozil Gufron; Titik Inayah; Junaidi Junaidi (Program Studi Agribisnis UIN Syarif Hidayatullah Jakarta, 2021)
This study aims to determine (1) the comparison of the cost structure of organic paddy farming (Sumber Urip Farmer Group) and inorganic paddy farming (Harta Jaya Farmer Group) in Watukebo Village, Blimbingsari District, Banyuwangi Regency, East Java. (2) the comparison of organic paddy farming (Sumber Urip Farmer Group) and Inorganic rice farming (Harta Jaya Farmer Group). The analysis tools used are cost analysis, income analysis, R / C ratio and two-sample t test differences. The results showed; (1) the total cost of organic paddy farming is IDR 11,042,735 / ha / one planting season, lower than the total cost of inorganic paddy which is IDR 11,154,570 / ha / one planting season. (2a) the average total income of organic paddy farming is IDR 27,048,320 / ha / one planting season and the average total income of inorganic paddy farming is IDR 26,681,500 / ha / one planting season. (2b) the average organic paddy farming revenue is IDR 16,005,585 / ha / one planting season. while inorganic paddy farming is IDR 15,526,930 / ha / one planting season. The average R / C ratio of organic and inorganic paddy farming, respectively, is 2.4 and 1.7, which means that organic paddy farming is more profitable and efficient than inorganic paddy farming in one planting season. (3) The results of the different test results of organic paddy farming and inorganic paddy farming have a significant difference. This is because the income of organic paddy farmers is greater than inorganic paddy. Keywords: Revenue, Farming, Organic, Inorganic AbstrakPenelitian ini bertujuan untuk mengetahui (1) perbandingan struktur biaya usahatani padi organik (Kelompok Tani Sumber Urip) dan usahatani padi Anorganik (Kelompok Tani Harta Jaya) di Desa Watukebo, Kecamatan Blimbingsari, Kabupaten Banyuwangi, Jawa Timur. (2) perbandingan pendapatan usahatani padi organik (Kelompok Tani Sumber Urip) dan usahatani padi Anorganik (Kelompok Tani Harta Jaya). Alat analisis yang digunakan analisis biaya, analisis pendapatan, R/C rasio dan Uji Beda dua sample t test. Hasil penelitian menunjukkan; (1) total biaya usahatani padi organik sebesar Rp 11,042,735/ha/satu musim tanam lebih rendah dibandingkan total biaya padi anorganik sebesar Rp 11,154,570/ha/ satu musim tanam. (2a) rata- rata total penerimaan usahatani padi organik sebesar Rp 27,048,320/ha/satu musim tanam dan rata-rata total penerimaan usahatani padi anorganik sebesar Rp 26,681,500/ha/satu musim tanam. (2b) Rata-rata pendapatan usahatani padi organik sebesar Rp 16,005,585 /ha/satu musim tanam. sedangkan usahatani padi anorganik yakni Rp 15,526,930/ha/satu musim tanam. Rata-rata R/C rasio usahatani padi organik dan padi anorganik secara urut yaitu 2,4 dan 1,7 yang berarti usahatani padi organik lebih menguntungkan dan efisien dibandingkan usahatani padi anorganik dalam satu musim tanam. (3) Hasil uji beda pendapatan usahatani padi organik dan padi anorganik terdapat perbedaan yang signifikan. Hal ini dikarenakan penerimaan petani padi organik lebih besar dibandingkan padi anorganik.Kata Kunci: Pendapatan, Usahatani, Organik, Anorganik This study aims to determine (1) the comparison of the cost structure of organic paddy farming (Sumber Urip Farmer Group) and inorganic paddy farming (Harta Jaya Farmer Group) in Watukebo Village, Blimbingsari District, Banyuwangi Regency, East Java. (2) the comparison of organic paddy farming (Sumber Urip Farmer Group) and Inorganic rice farming (Harta Jaya Farmer Group). The analysis tools used are cost analysis, income analysis, R / C ratio and two-sample t test differences. The results showed; (1) the total cost of organic paddy farming is IDR 11,042,735 / ha / one planting season, lower than the total cost of inorganic paddy which is IDR 11,154,570 / ha / one planting season. (2a) the average total income of organic paddy farming is IDR 27,048,320 / ha / one planting season and the average total income of inorganic paddy farming is IDR 26,681,500 / ha / one planting season. (2b) the average organic paddy farming revenue is IDR 16,005,585 / ha / one planting season. while inorganic paddy farming is IDR 15,526,930 / ha / one planting season. The average R / C ratio of organic and inorganic paddy farming, respectively, is 2.4 and 1.7, which means that organic paddy farming is more profitable and efficient than inorganic paddy farming in one planting season. (3) The results of the different test results of organic paddy farming and inorganic paddy farming have a significant difference. This is because the income of organic paddy farmers is greater than inorganic paddy. Keywords: Revenue, Farming, Organic, Inorganic